Ретроспективе и перспективе етнологије и антропологије - Šijaković (Serbia), Đurđina (Bulletin of the Institute of Ethnography SASA; Vol 66 No 1 (2018): Historical Retrospectives of Ethnology and Anthropology, 2018)
Ретроспективе и перспективе етнологије и антропологије